Murine Oncostatin M Has Opposing Effects on the Proliferation of OP9 Bone Marrow Stromal Cells and NIH/3T3 Fibroblasts Signaling through the OSMR - Lena Jakob (MDPI AG, 2021)
The IL-6 family cytokine Oncostatin M (OSM) is involved in cell development, growth, hematopoiesis, inflammation, and cancer. Intriguingly, OSM has proliferative and antiproliferative effects depending on the target cell. The molecular mechanisms underlying these opposing effects are not fully understood. Previously, we found OSM upregulation in different myeloproliferative syndromes. However, OSM receptor (OSMR) expression was detected on stromal cells but not the malignant cells themselves. In the present study, we, therefore, investigated the effect of murine OSM (mOSM) on proliferation in stromal and fibroblast cell lines. We found that mOSM impairs the proliferation of bone marrow (BM) stromal cells, whereas fibroblasts responded to mOSM with increased proliferation. When we set out to reveal the mechanisms underlying these opposing effects, we detected increased expression of the OSM receptors OSMR and LIFR in stromal cells. Interestingly, Osmr knockdown and Lifr overexpression attenuated the OSM-mediated effect on proliferation in both cell lines indicating that mOSM affected the proliferation signaling mainly through the OSMR. Furthermore, mOSM induced activation of the JAK-STAT, PI3K-AKT, and MAPK-ERK pathways in OP9 and NIH/3T3 cells with differences in total protein levels between the two cell lines. Our findings offer new insights into the regulation of proliferation by mOSM.